Epicardial Adipose Tissue and its Emerging Importance - Sadaf Shaheen; Nuzhat Hassan; Mohammed Asad Bilal Awan; Nosheen Zehra (ziauddin University, 2024)
It is an emerging concept now a day that epicardial adipose tissue (EAT) thickness has an essential character in the progression for cardiac risk profile. It is now consider as a new and consistent cardiovascular risk factor. EAT thickness is the indicator for cardiac adiposity. It modifies the cardiac morphology and function. It has close anatomical relation to myocardium. It causes local paracrine interactions between myocardial tissues. It causes enlargement of left ventricle with its diastolic dysfunction. Measurement and assessment of epicardial adipose tissue thickness is now done by new method echocardiography. It appraises visceral adiposity and inflammation. Association of EAT location and its physiological or pathological impor - tance requires advance research. EAT in future may replace waist circumference, as a marker of abdominal obesity. This article briefly discussion the structure of epicardial adipose tissue and its function. It also describes the method for its assessment. KEY WORDS: Epicardial adipose tissue thickness, Cardiac adipose tissue, Brown adipose tissue, Visceral adipose tissue